Data express gigabit junction with the next-generation Internet. - Collins, J.C (IEEE spectrum)
Important as a very high-performance backbone is to the next generation of the Internet, it is no less important that the points at which people connect to the backbone-the so-called points of presence, or POPs-provide an equivalent level of performance. For almost three years, members of the academic, research, and business community in the North Carolina region known as the Research Triangle-the area lying amid the cities of Raleigh, Durham, and Chapel Hill-have been working to create a high-performance regional network. As partners in the North Carolina Network Initiative (NCNI), they have built a network that can serve as a POP handling the multigigabit traffic to be delivered by the next-generation Internet. Thence comes its name: a GigaPOP. Like a great railway junction, the GigaPOP is a central distribution point where huge amounts of digital freight are moved between various end points and the main line (such as the very high-performance Backbone Network Services, or VBNS). The NCNI is one of a handful of regional networking organizations around the country. The others include the California Research and Education Network 2 (Calren2), the Metropolitan REN (MREN) serving the Chicago area, the Houston Area Computational Science Consortium (HACSC), and the New York State Educational and Research Network (Nysernet). NCNI's work, which predates most initiatives for the Internet's second generation, serves as a model of how various regions can latch onto the coming information superhighway to good effect